THE ANALYSIS OF RACIAL DISCRIMINATION IN SOLOMON NORTHUP’S 12 YEARS A SLAVE - Sarmita Utami Harahap; Fauziah Khairani Lubis (State University of Medan, 2018)
The research was focused on racial discrimination faced by the major characters and their resistances in 12 Years A Slave novel. This study was aimed This study was aimed to investigate the racial disrimination and the resistances in the novel. This study was conducted by applying descriptive qualitative method. The source of data was taken from 12 Years A Slave novel. The data are collected by using documentary techniques. Instrument for collecting the data is using documentary sheet. The results of this research were the racial discrimination and resistances happened in 12 Years A Slave. The racial discrimination in this novel happened towards the Black People and all discriminated people do the resistances to make their life better. As Northup is the main character so he got the most discrimination, then in the second position is Patsey and the last is Eliza Berry. Meanwhile the resistances done the most by Northup until he finally got freedom, and Patsey also did it twice and Eliza Berry did it three times. It can be concluded that the three major character who are slaves got discriminated and they did the resistances to save their life, even its only Northup who got the freedom in the end.